Identifying the association between cholesterol, blood pressure and weight with varied dietary habits, demographic and other factors - Thushani, C.; Thathsarani, U.S. (University of Jaffna, 2016)
Sri Lanka's health is the nation's wealth, but increment of total number of cholesterol, blood pressure and overweight patients are the crucial problem in health aspects. The aim of this study was to identify the relationship between hypertension, cholesterol, and overweight to the people who were with unhealthy lifestyle, demographic, social and other related factors. The researcher was utilized primary data and total of 300 individuals were included in this survey. Questionnaires were applied to collect the data of clinical participants from Bandarawela, Haputale, Balangoda and Ratnapura hospitals by using multistage and stratified sampling methods. Histograms, box plot, bar diagrams were used to present data graphically while Multivariate multiple regression analyses with MANOVA and Hoteling's 2 t used as statistical analyzing techniques. This research revealed that the majority of patients were consuming unhealthy diets such as excess consumption of salt, oil, eggs were caused in cholesterol and overweight. Lifestyle related risk factors such as excess body weight recorded by females, low levels of physical activity (unemployment), usage of cigarettes and usage of new technological equipment evident in cholesterol, hypertension and overweight. The results have highlighted lifestyle activities and dietary habits highly affected to the disease and programmes encouraging healthy dietary habits and weight reduction should be promoted at community level, as well as in clinical practice. Health education and counseling programmes for both patients and the public should be developed in order to increase awareness regarding healthy life style .
Keywords: Blood pressure; Cholesterol; Eating habits; Multivariate multiple regression; Overweight